Hospital-based palliative medicine : a practical, evidence-based approach - Pantilat, Steven; Anderson, Wendy; Gonzales, Matthew; Widera, Eric (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
"Hospital-Based Palliative Medicine: A Practical, Evidence-Based Approach focuses on improving a Hospitalist's ability to provide quality palliative care in the inpatient hospital setting. Although several large textbooks exist for the palliative care provider, there are few detailed resources aimed specifically at the general Hospitalist and hospital-based staff. Existing textbooks dedicate at most only one chapter to palliative care and they lack the detail and specificity in symptom management and communication skills to truly guide care. Hospital-Based Palliative Medicine addresses each of the major components involved in the delivery of inpatient palliative care. These include the management of complex symptoms and the use of specific communication techniques - right down to the actual words to say to the patient - to convey important information such as the reason for and use of medication and how to handle difficult topics with patients and their families and caregivers. The book's authors are all leaders in the field of palliative care, and most of them also practice as hospitalists, and thus understand both perspectives. Chapters are presented in a consistent format with particular attention to both clinical pearls and pitfalls, making the material practical and easily accessible to the busy hospitalist and associated hospital staff"--Provided by publisher.
7.4 Closing the Encounter7.5 Special Situations; References; Chapter 8 Family Meetings and Caring for Family Members; 8.1 Why Care for Families of Palliative Care Patients?; 8.2 Effective Communication with Family Members; 8.3 Additional Interprofessional Support for Families; References; Chapter 9 Assessing Goals of Care: A Case-Based Discussion; 9.1 Road Map For Discussing Goals of Care; 9.2 Use of Interpreters; 9.3 Conclusion; References; Chapter 10 Documenting Goals of Care and Treatment Preferences in the Hospital: A Case-Based Discussion; 10.1 Practical In-Hospital Documentation; 10.2 Troubleshooting.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Palliative Care -- methods; Evidence-Based Medicine -- methods; Hospitals; Palliative treatment; Evidence-based medicine; Hospital care; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Evidence-based medicine; Hospital care; Palliative treatment; Medical; Electronic books; Electronic books